Expression of TIA-1 and TIA-2 in T cell malignancies and T cell lymphocytosis. Issue 2 (February 1996) - Matutes, E; Coelho, E; Aguado, M J; Morilla, R; Crawford, A; Owusu-Ankomah, K; Catovsky, D
Abstract : OBJECTIVE: To investigate the reactivity with TIA-1 and TIA-2, two monoclonal antibodies that recognise, respectively, granular structures in T lymphocytes and the T cell receptor chain in cells from a variety of T cell disorders. METHODS: Cytoplasmic staining with TIA-1 and TIA-2 was carried out by the immunoalkaline phosphatase anti-alkaline phosphatase technique in 67 cases with a T cell disorder: 31 large granular lymphocyte (LGL) leukaemia, nine T-prolymphocytic leukaemia (T-PLL), five Sezary syndrome, four peripheral T cell lymphoma (PTCL), 13 T cell lymphocytosis, and five T-acute lymphoblastic leukaemia (T-ALL). All had over 75% abnormal T cells which were CD2+, CD3+, CD5+, CD7+, and negative with B cell markers. RESULTS: TIA-1 was positive in 77% cases of LGL leukaemia and half of the PTCL and T-ALL, whereas it was negative in all Sezary syndrome and most T-PLL (8/9) and reactive T-lymphocytosis (10/13). In LGL leukaemia, TIA-1 was positive irrespective of the membrane phenotype, whether CD8+, CD4- or CD4+, CD8-, and was more often positive in cases where cells were CD16+, CD56+, or CD57+. TIA-2 was positive in 60% of cases encompassing all diagnostic types of T cell disorder. There was no correlation between TIA-2 expression and that of other T cell markers, activation antigens, and natural killer markers. CONCLUSIONS: The pattern of TIA-1 expression in T cell malignancies may help in the differential diagnosis among LGL leukaemia (high expression), T cell lymphocytosis and other T cell diseases (low expression). As TIA-2 is expressed in over 95% mature T lymphocytes and thymic cells, its assessment may be useful to demonstrate aberrant phenotypes which can be exploited for detecting minimal residual disease.